1997
DOI: 10.1051/jp4:1997133
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sintering Conditions on the Power Loss Characteristics of Mn-Zn Ferrites for High Frequency Applications

Abstract: The sintering temperature significantly changed the microstmcture and effected the power loss behavior at the frequency range over 100kHz. The best power loss characteristics at 100kHz-200mT and 500kHz-50mT were obsemed in the samples sintered at 1300°C and 125OoC, respectively. Those results indicated that the power loss depended on the grain size, electrical resistivity and density of sintered cores. To maintain the stoichiometry at the sintering condition, the fenite cores were processed on the isocompositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…2(a), while samples sintered at 1400 1C posses much larger grains. The higher grain size for the samples sintered at 1400 1C may be attributed to the formation of Fe 2+ ions, which accelerate the growth rate of the grains [17,18]. Increase in grain size with zinc content can be seen in the photomicrographs shown in Figs Table 3 shows the compositional dependence of Curie temperature, T c , obtained from the inductance versus temperature profiles of different compositions.…”
Section: Article In Pressmentioning
confidence: 88%
“…2(a), while samples sintered at 1400 1C posses much larger grains. The higher grain size for the samples sintered at 1400 1C may be attributed to the formation of Fe 2+ ions, which accelerate the growth rate of the grains [17,18]. Increase in grain size with zinc content can be seen in the photomicrographs shown in Figs Table 3 shows the compositional dependence of Curie temperature, T c , obtained from the inductance versus temperature profiles of different compositions.…”
Section: Article In Pressmentioning
confidence: 88%
“…Samples sintered at 700 • C possess comparatively very small grains less than 1 m while samples sintered at 1300 • C possess much larger grains. The higher grain size for the sample sintered at 1300 • C may be attributed to the formation of Fe 2+ ions, which accelerate the growth rate of the grains [14,15]. It is observed that grain size of the samples under investigation is smaller than that prepared by ceramic method [16].…”
Section: Morphology (Sem)mentioning
confidence: 99%
“…For the accomplishment, a magnetic-slab embedded within the original dielectric substrate of an antenna in the prime H-field region beneath the patch reduced f o of a conventional patch, design a, with moderate impact on its performance and is perceived as a potential to miniaturisation. However, compared to a larger volume design with a 3D dielectric ridge, design c, performance needs to be improved to be fully considered as an alternative and is conjectured to be probable using forthcoming/pending magnetic materials with improved performance by means of better sintering conditions on the power loss [19] with high saturation magnetic flux density and low power loss at high temperature [20]. The magnetic-slab antenna can benefit from mixtures/composites with a higher degree of pure magnetic material (magnetization).…”
Section: Resultsmentioning
confidence: 99%